Effects of Rubber Factory Wastewater Sludge Compost on the Growth Parameters of Rubber Seedlings: A Nursery Study and Environmental Perspective - Anis Tatik Maryani; Aves Dwi Hendra; Miranti Sari Fitriani; Yudha Gusti Wibowo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Conducted at the University of Jambi's Teaching and Research Farm in Mendalo Indah Village, this three-month study from September to November 2022 utilized a Completely Randomized Design (CRD) with a single variable: rubber factory wastewater sludge compost application. Five treatment levels were tested: a0 = 25 g NPKMg dose, a1 = 100 g rubber factory wastewater sludge compost + 20 g NPKMg dose, a2 = 200 g rubber factory wastewater sludge compost + 15 g NPKMg dose, a3 = 300 g rubber factory wastewater sludge compost + 10 g NPKMg dose, and a4 = 400 g rubber factory wastewater sludge compost + 5 g NPKMg dose. Statistical analysis, employing ANOVA and the Honestly Significant Difference (HSD) test, determined treatment effects at a 5% significance level. The study assessed various rubber plant growth parameters, such as live seedling percentage, shoot emergence, budded shoot height, leaf count, stem diameter, root count, shoot and root dry weight. Notably, the application of 400 g of rubber factory wastewater sludge compost significantly influenced plant growth, specifically enhancing shoot emergence, stem diameter growth, and budded shoot height.